The Effect of Different Submerged Cage (Vietnamese Style) Depth on The Growth of Green Lobster (Panulirus homarus) in The East Coast of Pangandaran District - Rita Rostika; Iskandar Iskandar; Iwang Gumilar; Aulia Andhikawati; Muhammad Hafizh Arafi (International Journal Labs, 2023)
The purpose of this study was to determine the effect of submerged cage depth on the growth of green lobsters (Panulirus homarus) in Vietnamese-style cultivation on the East Coast of Pangandaran. The submerged cage was intended so that the lobsters are not disturbed by the situation/water quality in the upper layer of the water. The research method used a completely randomized design using 3 submerge cage depth treatments and 4 repetitions with different ones, A (2 meters); B (3.5 meters); and C (5 meters). Lobster maintenance was carried out for 40 days using a submerged cage with a diameter of 80 cm and a height of 90 cm. Each cage contains 10 lobster seeds measuring 40 g. Frequency of feeding 2 times a day. The amount of test feed given was 20% of the lobster weight each day. Measurement of water quality as supporting data was carried out at the beginning and end of the research. Sampling was done every 10 days and the observed parameters were growth rate, feed conversion ratio (FCR), and feed efficiency (FE). Lobster growth performance showed that treatment C (placement of cages at a depth of 5 meters) was the best among the others, as well as the daily growth rate (LPH) of 1.35%, feed conversion ratio (FCR) of 12.8, and feed efficiency ( EP) of 8.6%. The water quality in the submerged cage with a depth of 5 meters was DO 5.22 mg/L, the water temperature was 28 Celsius, pH was 7 and salinity was 34 ppt.